Perception And Preference of FEBI UINSU Students Regarding The Use of E-Payment: A Study Of Ease of Use, Financial Literacy, Trust Levels, And Behavoiral Patterns From an Islamic Economics Perspective - Syahrul Tanjung; Muhammad Syahbudi; Yenni Samri Juliati Nasution (Jurnal Investasi Islam, 2026)
This study aims to analyze the influence of perceived ease of use, financial literacy, level of trust, habitual behavior, and Islamic principles on students’ perceptions and preferences in using Sharia-based e-payment at Universitas Islam Negeri Sumatera Utara (UINSU). The study is motivated by the high level of e-payment usage among students, which is not fully accompanied by adequate financial literacy and understanding of Sharia principles. A quantitative approach was employed using a survey method, and the data were analyzed through multiple linear regression using two models: perception and preference. The sample size was 97 respondents, the sampling technique used was random sampling, with the sample size determined using the Slovin formula. The results indicate that all independent variables have a positive and significant effect on both perception and preference. Perceived ease of use is the most dominant variable in shaping perception (β = 0.282; sig. 0.001), while Islamic principles are the most dominant in shaping preference (β = 0.268; sig. 0.003). These findings suggest that students’ perceptions are primarily influenced by technical factors, whereas preferences are more strongly shaped by religious values and habitual usage. Therefore, strengthening digital financial literacy and understanding of Sharia principles is essential to promote more responsible and value-based use of e-payment.